Combination of the Probiotics Lacticaseibacillus rhamnosus GG and Bifidobacterium animalis subsp. lactis, BB-12 Has Limited Effect on Biomarkers of Immunity and Inflammation in Older People Resident in Care Homes: Results From the Probiotics to Reduce Infections iN CarE home reSidentS Randomized, Controlled Trial - Castro-Herrera, Vivian M.; Fisk, Helena L.; Wootton, Mandy; Lown, Mark; Owen-Jones, Eleri; Lau, Mandy; Lowe, Rachel; Hood, Kerenza; Gillespie, David; Hobbs, F. D. Richard; Little, Paul; Butler, Christopher C.; et al. (Frontiers in Immunology, 2021)
Ageing is associated with a decline in many components of the immune system (immunosenescence). Probiotics may improve the immune response in older people. The objective was to determine the effect of the combination of two probiotic organisms (Lacticaseibacillus rhamnosus GG (LGG) and Bifidobacterium animalis subsp. lactis, BB-12 (BB-12)) on a range of immune biomarkers measured in the blood of older people resident in care homes in the UK. In a randomised controlled trial, older people (aged 67 to 97 (mean 86) years) resident in care homes received the combination of LGG+BB-12 (1.3 to 1.6 x 109 CFU per day) or placebo for up to 12 months. Full blood count, blood immune cell phenotypes, plasma immune mediator concentrations, phagocytosis, and blood culture responses to immune stimulation were all measured. Response to seasonal influenza vaccination was measured in a subset of participants. Paired samples (i.e. before and after intervention) were available for 30 participants per group. LGG and BB-12 were more likely to be present in faeces in the probiotic group and were present at higher numbers. There was no significant effect of the probiotics on components of the full blood count, blood immune cell phenotypes, plasma immune mediator concentrations, phagocytosis by neutrophils and monocytes, and blood culture responses to immune stimulation. There was an indication that the probiotics improved the response to seasonal influenza vaccination with significantly (p = 0.04) higher seroconversion to the A/Michigan/2015 vaccine strain in the probiotic group than in the placebo group (47% vs 15%).